A Nabataean and Roman shrine with civic and military gods at Humayma, Jordan. (29th January 2019) - Reeves, M. Barbara
Abstract: The lifecycle of a Nabataean and Roman community shrine at Humayma, Jordan reflects the evolving values of the town's inhabitants from the first to the third century CE. This paper reviews the evidence for the shrine's appearance and significance over this period, as well as the nature of the cult practised there. Beginning its existence as a Nabataean shrine, whose design incorporated the rising sun and the town's primary peak, the building was damaged when the Romans converted Nabataea into Provincia Arabia . The Roman garrison initially dismantled the shrine to build their fort, but a few decades later the shrine was restored with a centrally placed Nabataean betyl and legionary altar symbolising harmony between the garrison and the town. The garrison's god, Jupiter‐Ammon‐Serapis, and possibly Isis, were now worshipped alongside the town's Nabataean deity. This shrine stressing military‐civilian harmony was later deliberately damaged, most likely during Zenobia's revolt.